Preliminary study of faecal cortisol and corticosterone as an index of acute cortisol secretion in the koala (Phascolarctos cinereus). Issue 12 (26th November 2013) - Johnston, SD; Booth, RA; Pyne, M; Keeley, T; Mackie, JT; Hulse, L; Ellis, W
<x xml:space="preserve">Abstract</x> Background Stress can play a role in disease incidence in all species via immunosuppression and has been implicated as a contributing factor in significant infectious diseases of koalas. Faecal cortisol measurement may represent a non‐invasive methodology for quantifying stress in koalas. Methods We used an ACTH (adrenocorticotropic hormone) stimulation test (10 IU) to induce sustained secretion of cortisol, which was measured in serum samples from four koalas and subsequently it was attempted to locate a corresponding elevation in either cortisol or corticosterone measurements within the faeces. Results Although ACTH administration resulted in an elevation of serum cortisol for at least 4 h post injection, it was not possible to identify a corresponding peak in corticosterone or cortisol concentrations in extracts from the faeces, consistent with the known gut transit time of the koala. Conclusion Faecal cortisol and corticosterone metabolites may not be reliable indices of acute changes in cortisol secretion in the koala and studies that attempt to use faecal cortisol as an index of stress will need to be interpreted with caution.